2019
DOI: 10.3389/fpsyt.2018.00776
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor Precursor in the Hippocampus Regulates Both Depressive and Anxiety-Like Behaviors in Rats

Abstract: Depression and anxiety are two affective disorders that greatly threaten the mental health of a large population worldwide. Previous studies have shown that brain-derived neurotrophic factor precursor (proBDNF) is involved in the development of depression. However, it is still elusive whether proBDNF is involved in anxiety, and if so, which brain regions of proBDNF regulate these two affective disorders. The present study aims to investigate the role of proBDNF in the hippocampus in the development of depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 56 publications
1
29
1
1
Order By: Relevance
“…As BDNF pro/+ mutant mice exhibited reduced mBDNF levels as a result of inefficient cleavage of proBDNF and spent more time immobile in the tail suspension test after being housed in social isolation, the stress of social isolation and impaired proBDNF cleavage may cooperatively promote depressive-like behavior. In line with these findings, it was reported that the ratio of mBDNF to proBDNF increases in mice subjected to chronic unpredicted mild stress that exhibit depressive-like behaviors [43] as well as in a rat model of anxiety induced by intraplantar injections of complete Freund's adjuvant and a model of depression induced by chronic restraint stress [44]. Moreover, a clinical report indicated that the mBDNF/proBDNF ratio in serum is a potential biomarker to discriminate patients with bipolar depression among those with depressive episodes [45].…”
Section: Discussionmentioning
confidence: 53%
“…As BDNF pro/+ mutant mice exhibited reduced mBDNF levels as a result of inefficient cleavage of proBDNF and spent more time immobile in the tail suspension test after being housed in social isolation, the stress of social isolation and impaired proBDNF cleavage may cooperatively promote depressive-like behavior. In line with these findings, it was reported that the ratio of mBDNF to proBDNF increases in mice subjected to chronic unpredicted mild stress that exhibit depressive-like behaviors [43] as well as in a rat model of anxiety induced by intraplantar injections of complete Freund's adjuvant and a model of depression induced by chronic restraint stress [44]. Moreover, a clinical report indicated that the mBDNF/proBDNF ratio in serum is a potential biomarker to discriminate patients with bipolar depression among those with depressive episodes [45].…”
Section: Discussionmentioning
confidence: 53%
“…Considering the different changes in BDNF in stress-related (decreased BDNF in hippocampus) and reward-related systems (increased BDNF in VTA and NAc), stress-induced anxiety and depression may be associated with the degree of activation of different pathways. Another study also demonstrated that both depressive and anxiety-like behaviors were related with the elevation of proBDNF in the hippocampus, whereas dendritic arborization and synaptophysin in neurons were differently regulated in these two phenotypes [32]. This research suggests the importance of morphological plasticity and supports the "neurotrophic hypothesis" [33], which postulates that stress-induced adverse phenotypes may be due to the loss of cells lacking neurotrophic maintenance.…”
Section: Bdnf Expression and Mood-related Brain Regionsmentioning
confidence: 57%
“…injected monoclonal anti-proBDNF antibody (McAb-proB) into mice before LPS treatment. The dose of 100 μg McAb-proB was found to fully block the biological function of the endogenous proBDNF without apparently affecting the behaviors in naïve mice [15,16,18,19]. Systemic administration of McAb-proB did not affect the weight changes induced by LPS injection (Fig.…”
Section: Systemic Mcab-prob Treatment Alleviated the Impaired Fear Mementioning
confidence: 89%
“…For investigating the role of monoclonal anti-proBDNF antibody (McAb-proB), mice were treated with intraperitoneal injection of 100 μg in 0.3 ml McAb-proB at 30 min before the induction of SAE model, or bilateral intracerebroventricular delivery (i.c.v) of 1 μg in 1 μl McAb-proB 3 days before LPS injection. The biological activity and safety of McAb-proB have been characterized by our previous studies [15,16,18,19]. Mouse IgG (CMCTAG, catalog: AT1596) were used for isotype control of related experiments.…”
Section: Drugs and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation